Galaxy merger histories and the role of merging in driving star formation at z > 1 - Kaviraj, S; Devriendt, J; Dubois, Y; Slyz, A; Welker, C; Pichon, C; Peirani, S; Borgne, D (Oxford University Press, 2015)

(untitled)
We use Horizon-AGN, a hydrodynamical cosmological simulation, to explore the role of mergers in the evolution of massive (M* > 1010 M⊙) galaxies around the epoch of peak cosmic star formation (1 < z < 4). The fraction of massive galaxies in major mergers (mass ratio R < 4: 1) is around 3 per cent, a factor of ∼2.5 lower than minor mergers (4: 1 < R < 10: 1) at these epochs, with no trend with redshift. At z ∼ 1, around a third of massive galaxies have undergone a major merger, while all remaining systems have undergone a minor merger. While almost all major mergers at z > 3 are ‘blue’ (i.e. have significant associated star formation), the proportion of ‘red’ mergers increases rapidly at z < 2, with most merging systems at z ∼ 1.5 producing remnants that are red in rest-frame UV–optical colours. The star formation enhancement during major mergers is mild (∼20–40 per cent) which, together with the low incidence of such events, implies that this process is not a significant driver of early stellar mass growth. Mergers (R < 10: 1) host around a quarter of the total star formation budget in this redshift range, with major mergers hosting around two-thirds of this contribution. Notwithstanding their central importance to the standard Λ cold dark matter paradigm, mergers are minority players in driving star formation at the epochs where the bulk of today's stellar mass was formed.